UNVEILING THE GENETIC BASIS OF BACTERIOCIN PRODUCTION FROM Enterococcus faecium ATCC 19434 - Wayah, Samson Baranzan; Tanko, Cynthia; Faila, Atika Abubakar; Yahaya, Godiya; Aji, Rebecca Jonah (FUDMA Journal of Sciences, 2024)
The prevalence of resistance to traditional antimicrobials is increasing rapidly, leading to a significant rise in annual deaths from antibiotic-resistant illnesses. In 2020, the global death toll from such diseases was approximately 500,000. If current trends continue, this figure could exceed 10 million by 2050, with associated economic damages surpassing 100 trillion USD. These alarming statistics highlight the urgent need for alternative antimicrobials. Bacteriocins are considered among the most promising options. Enterococcus faecium ATCC 19434 is known to produce a potent bacteriocin effective against Listeria monocytogenes and Staphylococcus aureus, though its specific bacteriocin and genetic properties have not been fully explored. This study aimed to identify the gene responsible for bacteriocin production in Enterococcus faecium ATCC 19434. DNA was extracted from the bacterium, and polymerase chain reaction (PCR) was conducted. The PCR products were analyzed through agarose gel electrophoresis, sequenced, and subjected to homology searches using the BLASTN and BLASTX tools from the National Center for Biotechnology Information (NCBI). Results revealed that Enterococcus faecium ATCC 19434 contains a gene encoding enterocin B. Additionally, it was found to harbor the gene for enterocin A immunity protein production. This discovery paves the way for future genetic modification of Enterococcus faecium ATCC 19434 to enhance enterocin B synthesis, facilitating its commercial application.
Keywords: Bacteriocin; Enterocin B; Enterocin A immunity protein; Genetic characterization